FTIR spectroscopy for estimation of efavirenz in raw material and tablet dosage form (International Current Pharmaceutical Journal, 2015)
A Fourier transform infrared (FTIR) spectrophotometric method was developed for rapid and direct measurement of efavirenz in pharmaceutical formulations. The method involves extraction of efavirenz from tablets with chloroform by sonication and the direct measurement of the absorbance in liquid phase using a reduced path length cell. In general, the spectrum was measured in transmission mode. The equipment was configured to collect a spectrum at 8 cm-1 resolution and 45 scans per sec .The spectra were collected between 4000 cm-1 and 450cm-1, the band obtained at 1750cm-1 (carbonyl group) showed intense, clear peak in the liquid phase for quantitation. The method was validated as per ICH guidelines. The method fulfilled most validation requirements in the linearity range 200-1000µg/mL. The coefficient of determination, limit of detection and quantification was found to be 0.993, 49.12?g/mL and 148.84?g/mL respectively. Results of developed FTIR method were compared with the results obtained with the existing UV method statistically by using t-test, which indicated that there is no significant difference between the methods at P=0.05. The proposed FTIR method reduces the solvent consumption and also eliminates the use of reagents. Thus the developed method offers a good alternative for the quantitative estimation of efavirenz in bulk and pharmaceutical dosage forms and also to quantify efavirenz when combined with other API in the same dosage form.International Current Pharmaceutical Journal, May 2015, 4(6): 390-395